Available nitrogen and methane emission from soils amended with organic manures and urea in rice-wheat system - SINGH, Y. V.; SHARMA, S. K. (Journal of Soil and Water Conservation, 2019)
A field experiment was conducted at ICAR-IARI, New Delhi for two years (2014-2016) with rice-wheat cropping system to estimate available nitrogen (NH4 +-N and NO3 --N) and methane emission from soil amended with different organic manures viz., FYM, vermicompost, Sesbania green manure and paddy straw. The experiment were laid out in rice and wheat crops comprising two tillage practices viz. puddled and non-puddled in rice and conventional tillage and no-tillage in wheat. There were seven treatments viz., T1: 120 kg N ha-1 through urea (control); T2: 120 kg N ha-1 + 5.0 t FYM ha-1; T3: 90 kg N ha-1 + 5.0 t FYM ha-1; T4:120 kg N ha-1 + 5.0 t GM ha-1 ; T5: 90 kg N ha-1 + 5.0 t GM ha-1; T6: 120 kg N ha-1 + 3.0 t vermicompost ha-1; T7: 90 kg N ha-1+ 3.0 t vermicompost ha-1 for rice crop. In wheat crop, paddy straw mulch was applied @ 5.0 t ha-1 and green manuring was replaced (T4 and T5) but rest treatments remained same as in rice. Results showed that addition of manure resulted in higher release of NH4 +-N and methane from rice fields and these values were higher in puddled plots than un-puddled plots. Contrary to it, NO3 —N was higher in wheat fields compared to rice fields. In puddled and non-puddled rice fields conditions, total cumulative emission of CH4 was lowest i.e., 38.3 and 20.8 kg ha-1, respectively in the control treatment and the highest (78.9 and 46.7 kg ha-1) in FYM + 100% nitrogen treatment. No-tillage had lower emission than conventional tillage in wheat supporting soils.